ANALISIS PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP PENGUNGKAPAN LAPORAN KEBERLANJUTAN (Studi Empiris pada Perusahaan yang Terdaftar pada BEI Tahun 2015-2018) - Rudolf Josua; Aditya Septiani (Diponegoro Journal of Accounting, 2020)
This research aims to examine the effect of the role of audit committee atributes that are proxied in independence of the audit committee, size of the audit committee, number of audit committee meetings and financial expertise of the audit committee on the sustainability report which is assessed using the ESG ScoreThis research population was non-financial sector companies listed ini Indonesia Stock Exchange in 2015-2018. The sampling method used in this research was purposive sampling method. With a sample of 46 companies during the observations period of 3 years in a row for totall of 184 samples. Analysis method of this research used multiple regressionThe results of this research showed that size of the audit committee and number of audit committee meetings significantly effect the disclosure of sustainability reports. While independence of the audit committee and audit committee financial expertise have a not significant effect on the disclosure of sustainability reports